Characterization of Cu10wt.%Al intermetallic coatings applied by the atmospheric plasma spraying process - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The atmospheric plasma spray process is one of the procedures used for the deposition of coatings resistant to wear due to friction, erosion, cavitation and corrosion. In this paper, the APS process produced a Cu10wt.%Al intermetallic coating which is a reliable candidate for use in tribological environments because of a combination of low price and exceptional resistance to abrasion under different work conditions. The aim of this study was to investigate the mechanical properties and the structure of the Cu10wt.%Al intermetallic coating and develop an efficient method for repairing and improving light alloy resistance to wear. Many components of copper alloys tend to be degraded due to corrosive environment, friction, erosion and cavitation. Such components can be saved by surface engineering with the use of appropriate coatings on surface areas exposed to degradation. A typical microstructure of a coating for the APS process is lamellar, with micro pores, unmelted particles, inter-lamellar oxides and precipitates present in it. The mechanical properties of Cu10wt.% Al coatings were investigated by measuring the microhardness of coating layers using the HV0.3 method while the bond strength was tested on a tensile machine. The morphologies of powder particles and the coating surfaces were analyzed on a scanning electron microscope (SEM). The analysis of the coating microstructure was carried out with the use of an optical microscope, and a share of micro pores was determined by analyzing the micrographs through an optical microscope (OM).
Keywords: Wearing; intermetallics; erosion; corrosion; Coatings; cavitation; Al; Abrasives